Dual Angiotensin Receptor and Neprilysin Inhibitor Ameliorates Portal Hypertension in Portal Hypertensive Rats - Shao-Jung Hsu; Hui-Chun Huang; Chiao-Lin Chuang; Ching-Chih Chang; Ming-Chih Hou; Fa-Yauh Lee; Shou-Dong Lee (MDPI AG, 2020)
Background: Portal hypertension is characterized by exaggerated activation of the renin-angiotensin-aldosterone axis. Natriuretic peptide system plays a counter-regulatory role, which is modulated by neprilysin. LCZ696 (sacubitril/valsartan) is a dual angiotensin receptor and neprilysin inhibitor. This study evaluated the effect of LCZ696 on portal hypertensive rats. Methods: Portal hypertension was induced by partial portal vein ligation (PVL) in rats. LCZ696, valsartan (angiotensin receptor blocker), or normal saline (control) was administered in PVL rats for 10 days. Then, hemodynamic and biochemistry data were obtained. The hepatic histology and protein expressions were surveyed. On the parallel groups, the portal-systemic shunting degrees were determined. Results: LCZ696 and valsartan reduced mean arterial pressure and systemic vascular resistance. LCZ696, but not valsartan, reduced portal pressure in portal hypertensive rats (control vs. valsartan vs. LCZ696: 15.4 ± 1.6 vs. 14.0 ± 2.3 vs. 12.0 ± 2.0 mmHg, control vs. LCZ696: P < 0.05). LCZ696 and valsartan improved liver biochemistry data and reduced intrahepatic Cluster of Differentiation 68 (CD68)-stained macrophages infiltration. Hepatic endothelin-1 (ET-1) protein expression was downregulated by LCZ696. The portal-systemic shunting was not affected by LCZ696 and valsartan. Conclusion: LCZ696 and valsartan reduced mean arterial pressure through peripheral vasodilation. Furthermore, LCZ696 significantly reduced portal pressure in PVL rats via hepatic ET-1 downregulation.